In Vivo Analysis of Anti-inflammatory, Analgesic, and Antipyretic Activities of Litsea elliptica Blume Leaf Extracts - Samsul, Raudhatun; Goh, May; Taha, Hussein; Ahmad, Norhayati (Trends in Sciences, 2026)
The leaves of Litsea elliptica have been traditionally claimed to be beneficial for the treatment of headaches, fever, itch, stomach ulcers, and cancer. This present study investigates the anti-inflammatory, analgesic, and antipyretic activities of the mature and young leaves of L. elliptica extracted via maceration (MACE) and microwave-assisted extraction (MAE) in animal models using adult male Wistar albino rats. Anti-inflammatory activity was assessed via carrageenan-induced paw oedema and xylene-induced ear oedema assays. Analgesic activity was determined using formalin-induced paw flinching test and acetic acid-induced writhing test. The brewer’s yeast-induced pyrexia assay was employed to determine the antipyretic properties of the extracts. The extraction methods did not influence the activity of mature leaf extracts across all the assays conducted. However, MAE seemed to enhance the anti-inflammatory and analgesic activities of young leaf extracts. Treatment with both mature and young leaf extracts attenuated inflammation, pain, and fever in the animal models at varying degrees of inhibition. Overall, our current findings highlighted the potential of L. elliptica leaves as novel anti-inflammatory, analgesic, and antipyretic agents. HIGHLIGHTS Litsea elliptica has been traditionally utilised across the countries of Southeast Asia as a remedy for many ailments, including headaches, fever, itch, stomach ulcers, and cancer. Pre-treatment with ethanolic mature and young leaf extracts reduced redness and swellings in the carrageenan-induced paw oedema and xylene-induced ear oedema. YMAE50 suppressed paw oedema by 96% while YMACE400 inhibited ear oedema by 72% relative to NC by the end of the assay. Young leaf extracts exhibited a potent analgesic effect, as evidenced by the marked reduction in the number of paw flinches and body writhes compared to NC. The progression of fever induced by brewer’s yeast was successfully mitigated following treatment with mature leaf extracts of elliptica, with an increase in rectal temperature remaining below 1 °C by the end of the assay. GRAPHICAL ABSTRACT